Passive bloodstains on cotton fabrics - Dicken, Lisa (Cranfield University, 2019)
Bloodstains on finished fabrics are frequently found at crime scenes, however there has been limited work on the creation mechanisms and interaction of blood and fabric. The initial aim of this research was to verify the use of a micro computed tomography (μCT) scanner for blood pattern analysis (BPA) research. The pilot study confirmed it was possible to visualise the form of the bloodstain inside the fabric in the CT scans, providing additional information to what could be learnt from examination of the external bloodstains alone. Bloodstains were created on three mass per unit areas (85.1, 163.5 and 224.6 g/m²) of laundered 100% cotton plain woven calico from six impact velocities (1.7, 2.9, 4.1, 4.9, 5.1 and 5.4 ms-1). The bloodstains were examined with external photographs, area measurements, a μCT scanner and a scanning electron microscope (SEM). The fabric with the lightest mass per unit area (85.1 g/m²) generally produced the largest bloodstains. The blood was able to coat the yarns owing to the high porosity of the fabric and wick along the low linear density yarns. For the fabrics with the middle (163.5 g/m²) and heaviest (224.6 g/m²) mass per unit areas less wicking occurred. Dry bloodstain area increased with impact velocity due to the increase in lateral spreading at impact with greater impact velocities. The yarn linear density, sett and yarn twist altered the way in which blood interacted with the fabrics. Bloodstains were then created on the calico fabrics following reactive dyeing or digital printing. The dry bloodstain areas increased for the dyed fabric owing to the swelling of the fibres following dyeing, reducing the intra-yarn spaces to a more optimum size for wicking. The digital printing increased the wettability of the fabric, most likely with a reduction in surface roughness. This allowed the blood to spread more easily on the surface of the fabric, before wicking into and along the intra-yarn spaces. The differences seen among the dry bloodstains for the different treatments emphasise the importance of not comparing bloodstains between fabrics with different finishing treatments.
© Cranfield University, 2019
Keywords: Micro Computed Tomography (MCT); Scanning electron microscopy; Wetting